West Africa spatial analysis prototype exploratory analysis: Cluster typing procedures - Rutstein, Shea O. (DHS Spatial Analysis Reports No. 4, 2000)
The West African Spatial Analysis Prototype is an attempt to gather existing demographic data collected through the Demographic and Health Surveys of countries in the West Africa region, identify their geographic coordinates, and place them within a geographic database and analysis system. These data are to be integrated with non-demographic data for geographic areas, such as climate, agriculture, etc. to provide more understanding and context to changes in demographic phenomena and the welfare of the population living in W.A. This understanding will help orient, plan, monitor, and evaluate programs to improve the health and welfare of the W.A. region.